2016
DOI: 10.1007/s10802-016-0237-6
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Impact of Cognitive Load and Motivation on Response Control in Relation to Delay Discounting in Children with ADHD

Abstract: Attention-deficit/hyperactivity disorder (ADHD) is characterized by deficits in impulse control across a range of behaviors, from simple actions to those involving complex decision-making (e.g., preference for smaller-sooner versus larger later rewards). This study investigated whether changes in motor response control with increased cognitive load and motivational contingencies are associated with decision-making in the form of delay discounting among 8-12 year old children with and without ADHD. Children wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 70 publications
2
9
0
Order By: Relevance
“…In the present study, after controlling for differences in IQ, there was a trend for children with elevated risk of ADHD as assessed by teacher report to show steeper discounting in the DD task than children at low risk, but not lower scores on the DoG task. The former finding corroborates and extends those studies in which children with clinically diagnosed ADHD show steeper discounting of real rewards over short delays (e.g., Martinelli et al, ; Yu et al, ). Unlike those studies, the present task used hypothetical rewards over much longer delay periods and tested children with elevated risk of ADHD on the basis of teacher ratings rather than on a clinical diagnosis.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…In the present study, after controlling for differences in IQ, there was a trend for children with elevated risk of ADHD as assessed by teacher report to show steeper discounting in the DD task than children at low risk, but not lower scores on the DoG task. The former finding corroborates and extends those studies in which children with clinically diagnosed ADHD show steeper discounting of real rewards over short delays (e.g., Martinelli et al, ; Yu et al, ). Unlike those studies, the present task used hypothetical rewards over much longer delay periods and tested children with elevated risk of ADHD on the basis of teacher ratings rather than on a clinical diagnosis.…”
Section: Discussionsupporting
confidence: 88%
“…Wilson, Mitchell, Musser, Schmitt, and Nigg () administered a DD task to 7‐ to 9‐year‐olds with and without a diagnosis of ADHD and found that discount functions were significantly steeper for the ADHD group, although this effect did not survive controlling for IQ. By comparison, Rosch and Mostofsky (), using the same hypothetical DD task as Wilson et al, found no difference in performance between an ADHD group and typically developing controls aged 8 to 12 years (see also Antonini, Becker, Tamm, & Epstein, ; Martinelli, Mostofsky, & Rosch, ).…”
Section: Inroductionmentioning
confidence: 93%
See 2 more Smart Citations
“…During adolescence and early adulthood, the ability to wait for reward, or delay gratification, is generally considered adaptive and is associated with better overall life outcomes (Banich et al, 2013; Steinbeis et al, 2016). Indeed, children and adolescents, as well as individuals with psychiatric conditions such as attention deficit hyperactive disorder and substance use disorders, reliably display elevated preference for immediate over delayed rewards (Martinelli et al, 2016; Perry and Carroll, 2008; Scheres et al, 2013, 2008). These disorders are also associated with, and have been in part attributed to, prefrontal cortical-mediated cognitive deficits.…”
Section: 0 Introductionmentioning
confidence: 99%